Methylene blue-functionalized blue/red dual-emissive carbon dots for ratiometric fluorescence detection of sunset yellow in food - Sihao Wang; Yifan Zhang; Dejin Lin; Jingqi Wang; Yihao Zhang; Siting Peng; Junyuan Shi; Siqi Xu; Da Chen (Analytica Chimica Acta, 2026)

Investigations on ballistic behaviour of additive manufactured 316L stainless steel corrugated sandwich panels filled with ultra-high performance geopolymer concrete - Jian Liu; Cunyi Li; Guobin Li; Sihao Lin; Ming-Xiang Xiong; Jianguang Fang (Engineering Structures, 2026)

Lightweight Fe3C-anchored three-dimensional interconnected carbon network composite: Integrating high electromagnetic interference shielding with joule heating and flame retardancy - Sihao Wu; Xiyu Qiu; Yucheng Qiao; Xiaofan Ma; Jianzhong Guo; Jing Zhang; Lin Chen (Chemical Engineering Journal, 2026)

Mechanism of heterogeneous mixing between typical oxygenated volatile organic compound and hematite: implication for radiative forcing - Yongpeng Ji; Linghao Kong; Jiaxin Wang; Baocong Zhao; Zhiming Zhang; Shengping Chen; Sihao Lin; Jiangyao Chen; Yanpeng Gao; Yuemeng Ji (Atmospheric Environment, 2026)

Genetic diversity of passion fruit germplasms analyzed by using start codon targeted (SCoT) markers - Jiaqi Zhang; Zhenjie Zhang; Yunqi Xu; Qingqing Zhu; Yulan Zhang; Zeyao Lin; Sihao Wu; Qiujin Lin; Li Jiang; Lijun Du; Zongqiang Shi; Xianqian Niu; et al. (Genetic Resources and Crop Evolution, 2026)

InceptionFormer: A deep learning framework for UAV LiDAR point cloud completion to improve tree parameters estimation in dense forests - Binhan Luo; Jian Yang; Shuo Shi; Ruilin Gan; Zhongliang Wu; Sihao Wang; Ao Wang; Lin Du; Wei Gong (Remote Sensing of Environment, 2026)

OH-initiated aqueous oxidation of methylglyoxal: Implications for organic acid and oligomer formation - Jiaxin Wang; Ying Chen; Wenjie Gao; Sihao Lin; Wenjian Li; Yongpeng Ji; Xiaolei Zhao; Yanpeng Gao; Yuemeng Ji; Taicheng An (Atmospheric Environment, 2026)

Enhancing anaerobic digestion of dairy wastewater with Fe3O4@BVRs: Performance and mechanisms - Zisheng Zhao; Haoyang Yu; Yixin Li; Huiyang Li; Sihao Lin; Yiming Ji; Yusen Li; Xiaowei Wang; Guangyi Zhang (Journal of Water Process Engineering, 2026)

Critical review on organic fouling in membrane distillation for desalination and water purification - Mingmei Ding; Sihao Zhang; Houzhen Zhou; Hang Xu; Hui Tao; Tao Lin; Li Gao (Desalination, 2025)

Covalently anchoring phosphorus nitride imide on carbon nanotubes for efficient electrochemical extraction of uranium - Sheng Li; Lin Zhao; Shiyong Wang; Changping Li; Lirong Cai; Sihao Lv; Gang Wang (Chemical Engineering Journal, 2024)

High-performance nonflammable gel polymer electrolyte with 3D interpenetrating network for advanced lithium-ion batteries - Yirou Du; Yuhui Xie; Lin Chen; Fei Hu; Xianshuai Liu; Sihao Yin; Hao Jiang; Xiaodong Liang; Feng Wu; Liang Qiao; Yi Mei; Delong Xie (Chemical Engineering Journal, 2024)

Electro-assisted anaerobic digestion of waste activated sludge for biomethane production enhanced by hyperosmosis of sodium chloride: Characteristics and microbial mechanisms - Xiaodong Xin; Jiaqian Xie; Yanfang Wang; Wenxuan Wei; Linjuan Li; Lin Li; Wei Li; Sihao Lv; Junguo He; Liguo Zhang (Process Safety and Environmental Protection, 2024)

Simultaneous Cu(II)-EDTA decomplexation and Cu(II) recovery using integrated contact-electro-catalysis and capacitive deionization from electroplating wastewater - Xiaoyan Shen; Shiyong Wang; Lin Zhao; Haoran Song; Wei Li; Changping Li; Sihao Lv; Gang Wang (Journal of Hazardous Materials, 2024)

Selective capture of uranium by p-block bismuth-based metal–organic framework - Lin Zhao; Zhihao Pan; Lirong Cai; Shiyong Wang; Bing Lu; Sihao Lv; Yongfu Qiu; Gang Wang (Desalination, 2024)

3D hierarchical fireproof gel polymer electrolyte towards high-performance and comprehensive safety lithium-ion batteries - Yirou Du; Xianshuai Liu; Lin Chen; Sihao Yin; Yuhui Xie; Ao Li; Xiaodong Liang; Yong Luo; Feng Wu; Yi Mei; Delong Xie (Chemical Engineering Journal, 2023)

Single-atom Zr embedded Ti4O7 anode coupling with hierarchical CuFe2O4 particle electrodes toward efficient electrooxidation of actual pharmaceutical wastewater - Anqi Wang; Xingxin Liu; Yukai Wen; Yongfu Qiu; Sihao Lv; Manman Xu; Cuilin Meng; Kai Wang; Fengjie Lin; Shuibo Xie; Qiongfang Zhuo (Water Research, 2023)

Copper removal and recovery from electroplating effluent with wide pH ranges through hybrid capacitive deionization using CuSe electrode - Shiyong Wang; Haohong Zhuang; Xiaoyan Shen; Lin Zhao; Zhihao Pan; Lizhi Liu; Sihao Lv; Gang Wang (Journal of Hazardous Materials, 2023)

Cofilin-1 induces acute kidney injury via the promotion of endoplasmic reticulum stress-mediated ferroptosis - Sihao Lin; Jie Wang; Bin Cao; Yang Huang; Xujun Sheng; Yingjian Zhu (Human Cell, 2023)
Ischemia–reperfusion injury (IRI) leads to acute kidney injury (AKI), which poses serious threat to public health and society. Many clinical studies were conducted to evaluate several biomarkers in AKI, among which Cofilin-1 remains to be a very promising one. To explore the potential mechanism of Cofilin-1 in AKI, we established an oxygen-glucose-deprivation (OGD)-induced AKI cell model. The overexpression and knock-down Cofilin-1 were used for gain- and loss-of-function. Pharmacological inhibitors were employed to study the related pathways. The results showed that Cofilin-1 was significantly upregulated in AKI cells, knocking down Cofilin-1 protected cells against the effect of OGD treatment and alleviated AKI phenotypes. Overexpression of Cofilin-1 might induce AKI by triggering ferroptosis, inhibiting NF-κB signaling or ER stress pathway attenuated Cofilin-1 induced lipid peroxidation and AKI. We also validated our findings in IRI-induced AKI mouse models in vivo. Our work elucidated that Cofilin-1 might induce AKI via promoting ER stress-mediated ferroptosis and argues it as a biomarker for early diagnosis of AKI. We also expect to offer novel insights on future therapeutic interventions.

Sludge source-redox mediators obtainment and availability for enhancing bioelectrogenesis and acidogenesis: Deciphering characteristics and mechanisms - Xiaodong Xin; Jiaqian Xie; Yanfang Wang; Lin Li; Wei Li; Sihao Lv; Zhidan Wen; Junguo He; Ying Xin (Water Research, 2023)

Toward sustainable inland aquaculture: Coastal subsidence monitoring in Taiwan - Wei-Chia Hung; Cheinway Hwang; Luigi Tosi; Shao-Hung Lin; Pei-Ching Tsai; Yi-An Chen; Wei-Ji Wang; En-Cheng Li; Sihao Ge (Remote Sensing Applications: Society and Environment, 2023)

Infant food production environments: A potential reservoir for vancomycin-resistant enterococci non-nosocomial infections - Zining Wang; Sihao Liao; Guanwen Huang; Mengyao Feng; Rui Yin; Lin Teng; Chenghao Jia; Yicheng Yao; Min Yue; Yan Li (International Journal of Food Microbiology, 2023)

Transient receptor potential ankyrin 1 contributes to the ATP-elicited oxidative stress and inflammation in THP-1-derived macrophage - Chao Tian; Xiaobo Han; Lang He; Feng Tang; Rongqi Huang; Zuoxian Lin; Shuai Li; Sihao Deng; Junjie Xu; Hualin Huang; Huifang Zhao; Zhiyuan Li (Molecular and Cellular Biochemistry, 2020)

Transient Receptor Potential Ankyrin 1 Contributes to Lysophosphatidylcholine-Induced Intracellular Calcium Regulation and THP-1-Derived Macrophage Activation - Chao Tian; Rongqi Huang; Feng Tang; Zuoxian Lin; Na Cheng; Xiaobo Han; Shuai Li; Peng Zhou; Sihao Deng; Hualin Huang; Huifang Zhao; Junjie Xu; et al. (The Journal of Membrane Biology, 2020)

Mortality in a Chinese chrysotile miner cohort - Xiaorong Wang; Sihao Lin; Eiji Yano; Hong Qiu; Igtanius T. S. Yu; Lapah Tse; Yajia Lan; Mianzhen Wang (International Archives of Occupational and Environmental Health, 2012)

Quality of life and its influencing factors among medical professionals in China - Siying Wu; Wei Zhu; Huangyuan Li; Ignatius Tak-Sun Yu; Sihao Lin; Xiaorong Wang; Shujuan Yang (International Archives of Occupational and Environmental Health, 2010)